CSR website disclosure: the influence of the upper echelons. Issue 2 (15th March 2019) - Everaert, Patricia; Bouten, Lies; Baele, Annelien
Abstract : Purpose: Using upper echelons theory (UET), the purpose of this paper is to unravel the influence of a CEO's ethical ideology on the presence of corporate social responsibility (CSR) disclosure on corporate websites. It also considers the CEO's perception of the importance of CSR (i.e. the extent of the CEO's detachment from the stockholder-oriented logic and attachment to the stakeholder-oriented logic). Design/methodology/approach: First, a survey was sent to CEOs of large unlisted Belgian companies. Its intention was to assess CEOs' ethical ideology along the idealism and relativism dimensions and their perceptions on the importance of CSR (PRESOR-detachment-from-stockholder view; PRESOR-attachment-to-stakeholder view), and to gather some demographics. Second, a content analysis of corporate websites was conducted so as to classify companies as being either CSR disclosing or non-disclosing. Third, the annual accounts of these corporations were investigated and follow-up phone calls were conducted to obtain data on managerial discretion (MD). Findings: CEOs' ethical ideology influences the degree to which they detach from the stockholder-oriented logic and attach to the stakeholder-oriented logic. Moreover, when MD is high, the degree of these CEOs' attachment to the stakeholder-oriented logic is the factor that influences the presence of CSR disclosure on their corporate websites. Finally, CEO's idealism indirectly influences the presence of CSR disclosure through the effect of idealism on the degree to which CEOs attach to the stakeholder-oriented logic. Originality/value: This paper shows that, when MD is high, CEOs' values and perceptions influence CSR disclosure decisions. This study thereby enhances our knowledge regarding the internal drivers of CSR disclosure practices and offers UET as a lens through which the importance of CEOs' personal characteristics in the decision-making process might be further explored.